Schetsen, Eerste bundel - Heijermans, Herman, 1864-1924 (Salt Lake City, UT : Project Gutenberg, 2010)
"Schetsen, Eerste bundel" by Herman Heijermans is a collection of short stories written in the early 20th century. The stories capture fleeting moments and observations of everyday life, often infused with a blend of introspection and social commentary that reflects the human experience and societal norms of the time. The work appears to delve into various characters and situations, highlighting the coexistence of beauty and sorrow in the mundane. The opening of the collection introduces readers to a character named Samuel Falkland, who leaves a gathering with three delicate white narcissi. As he navigates the city streets, he reflects on the beauty of the flowers against the backdrop of urban life, which is marked by his interactions with strangers. Falkland's initial appreciation for the narcissi turns into a contrast of emotions as he encounters a man who sullies their beauty with tobacco smoke, leading to feelings of hostility. This juxtaposition of beauty and degradation, as well as Falkland s contemplative nature, sets the tone for the stories that follow, inviting readers into a world rich with sensory details and personal reflections on life and relationships. (This is an automatically generated summary.)
Narcis -- Verhaaltje -- Huishouden -- Van een juffrouw -- Poes -- De Mof -- Tante Riek -- Nacht -- Bartje -- Binnenhuis-ideaal -- Droom -- Grootmoedertje -- Proletariërs -- Prinses Colibri -- Bloemen -- Meissie -- Warrem -- Fondant -- Grietje -- Schim -- Bal in een stal -- Mintenee -- Zusters -- Van twee ongetrouwde meisjes en een hond -- Doode -- Naaimugje -- Bloedspat -- Amstel -- Oudejaar -- Poppenwinkel -- Rouw -- Kliniek -- Avondverhaaltje -- Engagement -- Kamerhoek -- Gemengd bericht -- Kunstenaars-emotie -- Bezoek -- Dolce far niente -- Mopje -- Leeg verhaaltje -- Droge vrouwtje.
Release date is 2010-10-27
by Jeroen Hellingman and the Online Distributed Proofreading Team at https://www.pgdp.net/ for Project Gutenberg.
Keywords: Fiction